Effect of Dietary Supplement Yeast Culture on Production Performance and Hematological Parameters in Broiler Chicks - Saied , J.M.; Al-Jabary, Q.H.; Thalij, K.M. (International Journal of Poultry Science, 2011)
Twenty-one-day-old commercial broilers chicks (Ross) were used in completely randomized design to evaluate the efficacy of Saccharomyces cerevisiae (SC), grown at 3% Wheat Bran (WB) used solid state fermentation process to produce Yeast Culture (YC), on growth performance and hematological parameters. The YC production test revealed that the fermentation of WB significantly (p